Application of Developmental, Individual Differences, Relation-Based (DIR / Floortime) in Children with Developmental Disorders of the Neurological System and Brain - Sylvia Purnomo (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to determine the effectiveness of the application of Developmental, Individual, Relation-Based (DIR / Floortime) based therapy in children who experience disorders related to the neurological system and brain, such as autism and attention deficit disorder and hyperactivity. The application of this intervention is based on 3 basic principles, namely (1) developmental tasks, (2) differences in the neurological processes of each individual, and (3) affective relationships between parents / therapists and children. This systematic literature review was conducted in 7 journals based on predetermined inclusion and exclusion criteria. The results of the literature review show that the DIR / Floortime intervention is an intervention that can improve the communication ability of children with neurodevelopmental and brain disorders, especially autism. Parents are more adaptable in developing children's abilities according to their level of development. This intervention is also an ideal alternative intervention for the lower middle class so as not to spend too much special money to see professionals to get regular therapy.Penelitian ini bertujuan untuk mengetahui efektivitas penerapan terapi berbasis Developmental, Individual, Relation-Based (DIR/Floortime) pada anak-anak yang mengalami gangguan terkait sistem neurologis dan otak, seperti autis dan gangguan pemusatan perhatian dan hiperaktif. Penerapan intervensi ini berbasis pada 3 prinsip dasar, yaitu (1) tugas perkembangan, (2) perbedaan proses neurologis masing-masing individu, dan (3) hubungan afektif antara orang tua/terapis dengan anak. Ulasan tinjauan Pustaka sistematis ini dilakukan pada 7 jurnal berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan sebelumnya. Hasil ulasan literatur menunjukkan bahwa intervensi DIR/Floortime merupakan intervensi yang dapat meningkatkan kemampuan berkomunikasi anak dengan gangguan perkembangan saraf dan otak, khususnya autism. Orang tua lebih bisa beradaptasi dalam mengembangkan kemampuan anak sesuai dengan level perkembangannya. Intervensi ini juga merupakan alternatif intervensi yang cukup ideal bagi masyarakat kelas ekonomi menengah ke bawah agar tidak mengeluarkan biaya khusus terlalu banyak untuk menemui tenaga profesional demi mendapatkan terapi secara rutin.